2015
DOI: 10.1017/sjp.2015.20
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits, Future Time Perspective and Adaptive Behavior in Adolescence

Abstract: Several studies provide evidence of the importance of future time perspective (FTP) for individual success. However, little research addresses the relationship between FTP and personality traits, particularly if FTP can mediate their influence on behavior. In this study we analyze the mediating of FTP in the influence of personality traits on the way adolescents live their life at school. Sample consisted in 351 students, aged from 14 to 18 years-old, at different schooling levels. Instruments were the Portugu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…The domain of FTP on school and professional career is particularly relevant for adolescents as they have to make many important decisions and plans regarding their future education and career (Paixão & Silva, 2001). Studies have found that adolescents with higher levels of FTP involve less in maladaptive behaviours such as "facebook addiction" and academic cheating and more in adaptive school behaviours (Gomes Carvalho & Novo, 2015;Orosz et al, 2016;Przepiorka & Blachnio, 2016). Also, FTP on school and professional career has been found to influence adolescents' motivation for school (Schuitema et al, 2014), Consequently, in this study we focus on adolescents' FTP on school and professional career.…”
Section: Future Time Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The domain of FTP on school and professional career is particularly relevant for adolescents as they have to make many important decisions and plans regarding their future education and career (Paixão & Silva, 2001). Studies have found that adolescents with higher levels of FTP involve less in maladaptive behaviours such as "facebook addiction" and academic cheating and more in adaptive school behaviours (Gomes Carvalho & Novo, 2015;Orosz et al, 2016;Przepiorka & Blachnio, 2016). Also, FTP on school and professional career has been found to influence adolescents' motivation for school (Schuitema et al, 2014), Consequently, in this study we focus on adolescents' FTP on school and professional career.…”
Section: Future Time Perspectivementioning
confidence: 99%
“…Since Lewin's (1939) statement that behaviour is a function of both personal and situational characteristics, several FTP researchers have underlined the importance of personality and situational factors for attaining a FTP on school and career (Gomes Carvalho & Novo, 2015;Kairys & Liniauskaite, 2014;Morselli, 2013). However, only a few studies examined possible antecedents of FTP (e.g., Gomes Carvalho & Novo, 2015;Phan, 2014;Seginer, Vermulst, & Shoyer, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies about TP performed in academic contexts focus on the motivational impact of the subjective future. Generally, research has shown a positive and significant relationship between FTP and aca-demic achievement (Carvalho & Novo, 2015;De Volder & Lens, 1982;Lens & Tsuzuki, 2007;Peetsma and Van der Veen, 2011), motivation and self-regulated learning (de Bilde, Vansteenkiste, & Lens, 2011;Lens, Paixão, Herrera, & Grobler, 2012), and career adaptability (Janeiro, 2010;Marko & Savickas, 1998;Taber, 2013).…”
Section: Time Perspectivementioning
confidence: 99%
“…One of the main features of FTP that has a considerable impact on individuals' motivation and adaptation to different contexts is the connection between future goals and the present cognition and behaviours that it involves (Carvalho, 2015). Specifically, there is an instrumentality of present behaviour for the achievement of future goals (Lens et al, 2012), as well as an ability to delay gratification and cope with adversity in the present as a result of the definition of those goals (Carvalho and Novo, 2015). To this end, individuals' FTP tends to be related to their engagement in positive behaviours, such as increased motivation, persistence in tasks, and involvement in significant activities in the present, which ultimately leads to different adaptive pathways (Carvalho and Novo, 2015;Carvalho et al, 2010;Lens et al, 2012;Nuttin and Lens, 1985;Peetsma and van der Veen, 2011).…”
Section: Ftp and Behaviourmentioning
confidence: 99%